Investigation the injury patterns and reasons of the Turkish first leauge female volleyball players according to playing position - Ozhan Bavlı; Sibel Kucuk (Selcuk University, 2013)
The aim of this study was to investigate the injury patterns of Turkish first leauge women volleyball playersaccording to playing position. Totaly 84 firts leauge players who were average 24.1±7.5 years age and 11.4±4.7years sport age participated in to the sdudy voluntary. Data collected by using sport injury survey sheet whichwas developed by researcher. Survey investigated injury patterns whish were occured in last past 2 yaers.Survey analysis showed that % 77.3 of participant had injury before and injuries mostly (%62.1) accured intraining. Spiker was the most injured (%22.6) playing position, sprain was the most reported (%39.2) injury type,arm-shoulder was the most injured (%27.4) body part, overuse was the most injury reason (%47.3) and generallythe injuries needs more than four week for recovery time (%52.3). According to findings it is possible to say thatfor the preventing injuries in first leauge women volleyball players, trainers should set the training loadscarefully.